Raised under Stalin : young communists and the defense of socialism - Bernstein, Seth (Cornell University Press, 2017)
In Raised under Stalin, Seth Bernstein shows how Stalin's regime provided young people with opportunities as members of the Young Communist League or Komsomol even as it surrounded them with violence, shaping socialist youth culture and socialism more broadly through the threat and experience of war. Informed by declassified materials from post-Soviet archives, as well as films, memoirs, and diaries by and about youth, Raised under Stalin explains the divided status of youth for the Bolsheviks: they were the "new people" who would someday build communism, the potential soldiers who would defend the USSR, and the hooligans who might undermine it from within. Bernstein explains how, although Soviet revolutionary youth culture began as the preserve of proletarian activists, the Komsomol transformed under Stalin to become a mass organization of moral education; youth became the targets of state repression even as Stalin's regime offered them the opportunity to participate in political culture. Raised under Stalin follows Stalinist youth into their ultimate test, World War II. Even as the war against Germany decimated the ranks of Young Communists, Bernstein finds evidence that it cemented Stalinist youth culture as a core part of socialism.